2016
DOI: 10.1155/2016/3486727
|View full text |Cite
|
Sign up to set email alerts
|

An Immunomodulatory Device Improves Insulin Resistance in Obese Porcine Model of Metabolic Syndrome

Abstract: Obesity is associated with tissue inflammation which is a crucial etiology of insulin resistance. This inflammation centers around circulating monocytes which form proinflammatory adipose tissue macrophages (ATM). Specific approaches targeting monocytes/ATM may improve insulin resistance without the adverse side effects of generalized immunosuppression. In this regard, a biomimetic membrane leukocyte processing device, called the selective cytopheretic device (SCD), was evaluated in an Ossabaw miniature swine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…We have previously shown that ATMs are present in all relevant taxa of mammals [19]. Whereas the majority of studies with ATMs is centered on murine models of human obesity, some recent studies confirm that ATMs have a general metabolic and endocrine function in mammals [19,56,57]. In the present study, we show that ATMs are present in amphibian (X. laevis and A. mexicanum) WAT, which suggests that they are evolutionarily conserved constituents of WAT immune cell population in vertebrates.…”
Section: Discussionsupporting
confidence: 60%
“…We have previously shown that ATMs are present in all relevant taxa of mammals [19]. Whereas the majority of studies with ATMs is centered on murine models of human obesity, some recent studies confirm that ATMs have a general metabolic and endocrine function in mammals [19,56,57]. In the present study, we show that ATMs are present in amphibian (X. laevis and A. mexicanum) WAT, which suggests that they are evolutionarily conserved constituents of WAT immune cell population in vertebrates.…”
Section: Discussionsupporting
confidence: 60%
“…It follows that the preferential sequestration of inflammatory CD14 hi monocytes is enhanced in the low iCa environment. The selectivity of binding of the highest activated leukocytes has been repeatedly observed in preclinical animal models where systemic CD11R3: the porcine analog of human CD11b (21), levels decrease through the treatment course (10,11,22,23). This effect was measured directly in a clinical trial by comparing the CD11R3 relative fluorescence of the circulating cells in the peripheral blood to those directly associated with the SCD (24).…”
Section: A Serendipitous Discoverymentioning
confidence: 98%
“…This effect was measured directly in a clinical trial by comparing the CD11R3 relative fluorescence of the circulating cells in the peripheral blood to those directly associated with the SCD (24). These results when taken together (10,11,(22)(23)(24)(25), suggest a SCD mechanism of action with a simultaneous, combination effect to transiently sequester activated circulating neutrophils and monocytes, with enhanced selectivity for inflammatory leukocytes, which alters the overall activation of bound and processed leukocytes. Clinical efficacy in AKI with Multi-Organ Dysfunction (MOD) may be due to sequestration and immunomodulation of leukocytes in the SCD.…”
Section: A Serendipitous Discoverymentioning
confidence: 99%
“…4,5 Extensive experimental studies have shown that inflammation is closely linked with hypertension, obesity and diabetes, 6,7 while clinical studies have demonstrated that obese diabetic patients have increased total leukocyte counts, which are correlated with insulin sensitivity and partially mediated by inflammatory changes in adipose tissue. 8,9 Thus, chronic, low-grade inflammation contributes to the development of cardiometabolic diseases.…”
Section: Introductionmentioning
confidence: 99%